Pengaruh Kesadaran Lingkungan Terhadap Penerapan Akuntansi Lingkungan Di Sektor Usaha Mikro Kecil Dan Menengah (UMKM) - Arifah Nurmalika; Ersi Sisdianto (CV. KAMPUSA AKADEMIK PUBLISHING, 2025)
This study aims to analyse the impact of environmental awareness on the application of environmental accounting in the Micro, Small and Medium Enterprises (MSME) sector. In a global context where sustainability is increasingly emphasised, environmental awareness is an important factor influencing business practices. This study uses a literature review to understand the relationship between environmental awareness and the application of environmental accounting. Several academic sources, journal articles and related reports were reviewed. The literature review shows that MSME owners are more environmentally aware, which contributes to better use of environmental accounting. This includes effective resource management, clear reporting of sustainability practices and measurement of the business impact on the environment. The study found that education and training that increases environmental awareness can encourage MSMEs to adopt better environmental accounting practices that support economic and environmental sustainability goals. Suggestions for further research, such as empirical studies to test these findings in the field, are also included.